Binder composition for all-solid-state secondary batteries, slurry composition for an electrode composite layer of an all-solid-state secondary battery, slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, and an all-solid-state secondary battery
A binder composition with specific monomer unit ratios and Mooney viscosity enhances adhesion and flexibility, addressing the output and cycle performance issues in all-solid-state secondary batteries.
Patent Information
- Application Number
- KR1020217002819
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-08-31
- Filing Date
- 2019-08-22
- Publication Date
- 2026-11-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional binder compositions for all-solid-state secondary batteries do not adequately enhance output characteristics and high-temperature cycle characteristics.
A binder composition comprising a polymer with specific ratios of nitrile group-containing monomer units and aliphatic conjugated diene monomer units, along with a Mooney viscosity greater than or equal to 65, is used to form solid electrolyte-containing layers, improving adhesion and flexibility.
The composition forms solid electrolyte-containing layers with excellent output characteristics and high-temperature cycle characteristics in all-solid-state secondary batteries.
Smart Images

Figure 112021010968494-PCT00001 
Figure 112021010968494-PCT00002
Abstract
Description
Technology Field
[0001] The present invention relates to a binder composition for an all-solid-state secondary battery, a slurry composition for an electrode composite layer of an all-solid-state secondary battery, a slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, and an all-solid-state secondary battery. Background Technology
[0002] In recent years, the demand for secondary batteries, such as lithium-ion batteries, has been increasing in various applications, including small home power storage devices, motorcycles, electric vehicles, and hybrid electric vehicles, in addition to portable terminals such as portable information terminals and portable electronic devices. Furthermore, with the expansion of applications, there is a growing requirement for secondary batteries to further enhance safety.
[0003] Accordingly, all-solid-state secondary batteries using solid electrolytes are attracting attention as highly safe secondary batteries, replacing organic solvent electrolytes which are highly flammable and pose a high risk of ignition in the event of leakage. The solid electrolyte is contained within the all-solid-state secondary battery as a solid electrolyte-containing layer (electrode composite layer, solid electrolyte layer) formed by binding components, such as the solid electrolyte, together, for example, by a binder.
[0004] Here, generally, in an all-solid-state secondary battery, a solid electrolyte layer is disposed between electrodes (positive and negative electrodes) having an electrode composite layer on a current collector. And, for the fabrication of a solid electrolyte-containing layer, such as an electrode composite layer or a solid electrolyte layer, a binder composition for an all-solid-state secondary battery containing a polymer as a binder is used. Specifically, for the formation of the solid electrolyte-containing layer, a slurry composition for a solid electrolyte-containing layer prepared using the binder composition is used.
[0005] For example, an electrode composite layer can be formed by drying a slurry composition for an all-solid-state secondary battery electrode composite layer comprising a binder composition, a solid electrolyte, and an electrode active material (hereinafter abbreviated as "slurry composition for electrode composite layer"). In addition, a solid electrolyte layer can be formed by drying a slurry composition for an all-solid-state secondary battery solid electrolyte layer comprising a binder composition and a solid electrolyte (hereinafter abbreviated as "slurry composition for solid electrolyte layer").
[0006] In addition, attempts have been made to improve the performance of all-solid-state secondary batteries by improving the binder material included in the binder composition.
[0007] Specifically, for example, in Patent Document 1, a polymer having a polymerization unit having a nitrile group in a content ratio of 2 to 30 mass% and an iodine value of 0 mg / 100 mg or more and 30 mg / 100 mg or less is used as a binder to form a solid electrolyte containing layer, thereby improving the output characteristics and high-temperature cycle characteristics of an all-solid-state secondary battery having said solid electrolyte containing layer. Prior art literature
[0008] Japanese Patent No. 5768815 The problem to be solved
[0009] However, the binder composition containing the above-mentioned conventional binder had room for improvement in terms of further enhancing the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery.
[0010] Accordingly, the present invention aims to provide a binder composition for an all-solid-state secondary battery capable of forming a solid electrolyte-containing layer that can exhibit excellent output characteristics and high-temperature cycle characteristics in the all-solid-state secondary battery.
[0011] In addition, the present invention aims to provide a slurry composition for an electrode composite layer for an all-solid-state secondary battery that can form an electrode composite layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0012] In addition, the present invention aims to provide a slurry composition for a solid electrolyte layer of an all-solid-state secondary battery capable of forming a solid electrolyte layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0013] In addition, the present invention aims to provide an all-solid-state secondary battery having excellent output characteristics and high-temperature cycle characteristics. means of solving the problem
[0014] The inventors conducted thorough investigations with the aim of solving the above problem. The inventors discovered that when forming a solid electrolyte-containing layer, such as an electrode composite layer and a solid electrolyte layer, a polymer having a Mooney viscosity greater than or equal to a predetermined value can be used as a binder to include nitrile group-containing monomer units and aliphatic conjugated diene monomer units in proportions within a predetermined range, thereby enabling excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery, and thus completed the present invention.
[0015] That is, the present invention aims to advantageously solve the above problem. The binder composition for an all-solid-state secondary battery according to the present invention is a binder composition for an all-solid-state secondary battery comprising polymer A, wherein polymer A comprises nitrile group-containing monomer units and aliphatic conjugated diene monomer units, wherein the content ratio of the nitrile group-containing monomer units in polymer A is 5 mass% or more and 30 mass% or less, and the content ratio of the aliphatic conjugated diene monomer units is 40 mass% or more and 95 mass% or less, and wherein the Mooney viscosity (ML) of polymer A 1+4It is characterized by having a temperature of 65 or higher (100°C). In this way, by using a binder composition containing a polymer A having a Mooney viscosity greater than or equal to the value described above, while containing nitrile group-containing monomer units and aliphatic conjugated diene monomer units in proportions within the range described above, it is possible to form a solid electrolyte-containing layer (electrode composite layer and solid electrolyte layer) capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0016] Meanwhile, in the present invention, "comprising monomer units" means "a repeating unit derived from the monomer is included in the polymer obtained using the monomer." Here, the ratio of each repeating unit (monomer unit) constituting the polymer to the polymer is 1 H-NMR and 13 It can be measured using nuclear magnetic resonance (NMR) methods such as C-NMR.
[0017] In addition, in the present invention, the "Mooney viscosity (ML)" of the polymer 1+4 ", 100℃)" can be measured in accordance with JIS K6300-1.
[0018] Here, the binder composition for an all-solid-state secondary battery according to the present invention preferably has a content ratio of ethylene unsaturated carboxylic acid ester monomer units in the polymer A of 0 mass% or more and 50 mass% or less. If the content ratio of ethylene unsaturated carboxylic acid ester monomer units in the polymer A is within the range described above, the output characteristics of the all-solid-state secondary battery can be further improved.
[0019] In addition, the binder composition for an all-solid-state secondary battery of the present invention preferably has an iodine value of polymer A greater than 30 mg / 100 mg. If the iodine value of polymer A exceeds the value described above, the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery can be further improved.
[0020] Meanwhile, in the present invention, the "iodine value" of the polymer can be measured in accordance with JIS K6235 (2006).
[0021] Here, the binder composition for an all-solid-state secondary battery according to the present invention further comprises a solvent, and it is preferable that the solvent contains at least one of xylene and butyl butyrate. By using a binder composition comprising xylene and / or butyl butyrate as the solvent, the adhesion and flexibility of the solid electrolyte-containing layer can be increased, while further improving the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery.
[0022] In addition, the present invention aims to advantageously solve the above problem, and the slurry composition for an electrode composite layer of an all-solid-state secondary battery according to the present invention is characterized by comprising a solid electrolyte, an electrode active material, and any one of the all-solid-state secondary battery binder compositions described above. Thus, by using a slurry composition for an electrode composite layer comprising a solid electrolyte, an electrode active material, and any one of the binder compositions described above, it becomes possible to form an electrode composite layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0023] Here, in the slurry composition for the electrode composite layer of the all-solid-state secondary battery according to the present invention, it is preferable that the solid electrolyte is an amorphous sulfide containing Li and P. If an amorphous sulfide containing Li and P is used as the solid electrolyte, the output characteristics of the all-solid-state secondary battery can be further improved.
[0024] In addition, in the slurry composition for the electrode composite layer of the all-solid-state secondary battery according to the present invention, the solid electrolyte is preferably a sulfide glass composed of Li2S and P2S5. If a sulfide glass composed of Li2S and P2S5 is used as the solid electrolyte, the output characteristics of the all-solid-state secondary battery can be further improved.
[0025] In addition, the present invention aims to advantageously solve the above problem, and the slurry composition for a solid electrolyte layer of an all-solid-state secondary battery according to the present invention is characterized by comprising a solid electrolyte and any one of the binder compositions for an all-solid-state secondary battery described above. In this way, by using a slurry composition for a solid electrolyte layer comprising a solid electrolyte and any one of the binder compositions described above, it becomes possible to form a solid electrolyte layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0026] Here, in the slurry composition for the solid electrolyte layer of the all-solid-state secondary battery according to the present invention, it is preferable that the solid electrolyte is an amorphous sulfide containing Li and P. If an amorphous sulfide containing Li and P is used as the solid electrolyte, the output characteristics of the all-solid-state secondary battery can be further improved.
[0027] In addition, in the slurry composition for the solid electrolyte layer of the all-solid-state secondary battery of the present invention, it is preferable that the solid electrolyte is a sulfide glass composed of Li2S and P2S5. If a sulfide glass composed of Li2S and P2S5 is used as the solid electrolyte, the output characteristics of the all-solid-state secondary battery can be further improved.
[0028] In addition, the present invention aims to advantageously solve the above problem. The all-solid-state secondary battery of the present invention is characterized by having at least one of an electrode having an electrode composite layer formed using any one of the all-solid-state secondary battery electrode composite layer slurry compositions described above, and a solid electrolyte layer formed using any one of the all-solid-state secondary battery solid electrolyte layer slurry compositions described above. In this way, if at least one solid electrolyte-containing layer is formed using a slurry composition for a solid electrolyte-containing layer comprising the binder composition described above, excellent output characteristics and high-temperature cycle characteristics can be exhibited in the all-solid-state secondary battery. Effects of the invention
[0029] According to the present invention, a binder composition for an all-solid-state secondary battery capable of forming a solid electrolyte-containing layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in the all-solid-state secondary battery can be provided.
[0030] In addition, according to the present invention, a slurry composition for an electrode composite layer for an all-solid-state secondary battery can be provided, which can form an electrode composite layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0031] In addition, according to the present invention, a slurry composition for a solid electrolyte layer of a solid-state secondary battery can be provided, which can form a solid electrolyte layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in a solid-state secondary battery.
[0032] In addition, according to the present invention, an all-solid-state secondary battery with excellent output characteristics and high-temperature cycle characteristics can be provided. Specific details for implementing the invention
[0033] Hereinafter, embodiments of the present invention will be described in detail.
[0034] Here, the binder composition for an all-solid-state secondary battery of the present invention can be used for manufacturing an all-solid-state secondary battery, and, for example, can be used in the preparation of a slurry composition for a solid electrolyte-containing layer (slurry composition for an all-solid-state secondary battery electrode composite layer and / or slurry composition for an all-solid-state secondary battery solid electrolyte layer) used in the manufacture of a solid electrolyte-containing layer (electrode composite layer and / or solid electrolyte layer) constituting an all-solid-state secondary battery. In addition, the slurry composition for an electrode composite layer of an all-solid-state secondary battery of the present invention includes the binder composition for an all-solid-state secondary battery of the present invention and can be used for forming an electrode composite layer. In addition, the slurry composition for a solid electrolyte layer of an all-solid-state secondary battery of the present invention includes the binder composition for an all-solid-state secondary battery of the present invention and can be used for forming a solid electrolyte layer. And, the all-solid-state secondary battery of the present invention uses a slurry composition for a solid electrolyte-containing layer comprising the binder composition for an all-solid-state secondary battery of the present invention in the formation of at least one solid electrolyte-containing layer among a positive electrode composite layer, a negative electrode composite layer, and a solid electrolyte layer.
[0035] (Binder composition for all-solid-state secondary batteries)
[0036] The binder composition of the present invention contains at least a binder and optionally may further contain a solvent and other components. Here, the binder composition of the present invention contains, as the binder, a polymer A having a ratio of 5 mass% or more and 30 mass% or less of nitrile group-containing monomer units and a ratio of 40 mass% or more and 95 mass% or less of aliphatic conjugated diene monomer units, and also having a Mooney viscosity of 65 or higher.
[0037] In addition, according to the binder composition of the present invention comprising the polymer A described above, a solid electrolyte-containing layer (electrode composite layer and / or solid electrolyte layer) capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery can be formed.
[0038] Meanwhile, the reason why a solid electrolyte-containing layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery can be formed by using the binder composition of the present invention is not clear, but is presumed to be as follows.
[0039] That is, the polymer A included as a binder in the binder composition of the present invention includes a nitrile group-containing monomer unit in a ratio of 5 mass% or more, thereby ensuring adsorption capacity to the solid electrolyte, while solubility in the solvent included in the slurry composition for the solid electrolyte-containing layer is ensured because the content ratio of the nitrile group-containing monomer unit is 30 mass% or less. Therefore, by including the nitrile group-containing monomer unit in the polymer A in a ratio of 5 mass% or more and 30 mass% or less, the polymer A dissolves in the solvent within the slurry composition for the solid electrolyte-containing layer and is adsorbed well to the solid electrolyte, thereby increasing the dispersibility of the solid electrolyte. Furthermore, according to the slurry composition for the solid electrolyte-containing layer in which the solid electrolyte is well dispersed, a solid electrolyte-containing layer in which the solid electrolyte is well distributed can be formed.
[0040] In addition, the aliphatic conjugated diene monomer unit included in the polymer A as the binder described above is a repeating unit capable of imparting flexibility to polymer A. That is, by including the aliphatic conjugated diene monomer unit in polymer A at a ratio of 40 mass% or more, polymer A has appropriate flexibility, thereby ensuring the flexural resistance of the solid electrolyte-containing layer formed from the slurry composition for the solid electrolyte-containing layer containing the binder composition. On the other hand, since the content ratio of the aliphatic conjugated diene monomer unit is 95 mass% or less, the decrease in adhesion of the solid electrolyte-containing layer caused by the decrease in strength of polymer A can be suppressed.
[0041] In addition, polymer A as a binder described above has excellent flexibility and binding ability because its Mooney viscosity is 65 or higher.
[0042] In this way, polymer A as a binder contains nitrile group-containing monomer units and aliphatic conjugated diene monomer units in proportions within the ranges described above, while simultaneously having a Mooney viscosity greater than or equal to the value described above, thereby forming a solid electrolyte-containing layer in which the solid electrolyte is well distributed and has excellent flexibility and adhesion. Furthermore, it is believed that such a solid electrolyte-containing layer can improve the battery characteristics (output characteristics and high-temperature cycle characteristics) of an all-solid-state secondary battery.
[0043] <Binding Material>
[0044] As described above, the binder composition of the present invention comprises, as a binder, a nitrile group-containing monomer unit and an aliphatic conjugated diene monomer unit, each in a ratio within a predetermined range, and also comprises a polymer A having a Mooney viscosity greater than or equal to a predetermined value. Meanwhile, the binder composition of the present invention may also contain a binder other than polymer A (other binders).
[0045] <<Composition of Polymer A>>
[0046] [Nitrile group-containing monomer unit]
[0047] Examples of nitrile group-containing monomers capable of forming nitrile group-containing monomer units include α,β-ethylenedimethyl unsaturated nitrile monomers. Specifically, α,β-ethylenedimethyl unsaturated nitrile monomers are not particularly limited as long as they are α,β-ethylenedimethyl unsaturated compounds having nitrile groups, but examples include acrylonitrile; α-halogenoacrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; and α-alkylacrylonitrile such as methacrylonitrile and α-ethylacrylonitrile. Among these, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred, from the perspective of further improving the output characteristics and high-temperature cycle characteristics of an all-solid-state secondary battery. Meanwhile, one type of nitrile group-containing monomer may be used alone, or two or more types may be combined in any ratio.
[0048] In addition, the content ratio of the nitrile group-containing monomer unit in polymer A needs to be 5 mass% or more and 30 mass% or less when the total amount of repeating units contained in polymer A is 100 mass%, it is preferable that it be 8 mass% or more, more preferable that it be 12 mass% or more, preferable that it be 28 mass% or less, more preferable that it be 26 mass% or less, and even more preferable that it be 20 mass% or less. If the content ratio of the nitrile group-containing monomer unit in polymer A is less than 5 mass%, the binding ability of polymer A is reduced, so it is not possible to prepare a slurry composition for a solid electrolyte-containing layer in which the solid electrolyte is well dispersed. Consequently, the output characteristics and high-temperature cycle characteristics of an all-solid-state secondary battery having a solid electrolyte-containing layer formed using the slurry composition for a solid electrolyte-containing layer are reduced. Meanwhile, if the content ratio of the nitrile group-containing monomer unit in polymer A exceeds 30 mass%, the solubility of polymer A in a solvent is reduced, so it is not possible to prepare a slurry composition for a solid electrolyte-containing layer in which the solid electrolyte is well dispersed. Consequently, the output characteristics and high-temperature cycle characteristics of an all-solid-state secondary battery having a solid electrolyte-containing layer formed using the slurry composition for a solid electrolyte-containing layer are reduced.
[0049] [Aliphatic conjugated diene monomer unit]
[0050] Aliphatic conjugated diene monomers capable of forming aliphatic conjugated diene monomer units are not particularly limited and include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, etc. Among these, 1,3-butadiene is preferred from the perspective of further improving the output characteristics and high-temperature cycle characteristics of an all-solid-state secondary battery while sufficiently ensuring the flexibility of the solid electrolyte-containing layer. Meanwhile, one type of aliphatic conjugated diene monomer may be used alone, or two or more types may be used in combination in any ratio.
[0051] In addition, the content ratio of aliphatic conjugated diene monomer units in polymer A needs to be 40 mass% or more and 95 mass% or less when the total amount of repeating units contained in polymer A is 100 mass%, and it is preferable that it be 45 mass% or more, more preferable that it be 55 mass% or more, even more preferable that it be 60 mass% or more, preferable that it be 92 mass% or less, and more preferable that it be 88 mass% or less. If the content ratio of aliphatic conjugated diene monomer units in polymer A is less than 40 mass%, the flexibility of polymer A is reduced, so good flexural resistance cannot be imparted to the solid electrolyte-containing layer. Consequently, the output characteristics and high-temperature cycle characteristics of an all-solid-state secondary battery equipped with a solid electrolyte-containing layer are reduced. On the other hand, if the content ratio of aliphatic conjugated diene monomer units in polymer A exceeds 95 mass%, the strength of polymer A is reduced, so good adhesion cannot be imparted to the solid electrolyte-containing layer. As a result, the output characteristics and high-temperature cycle characteristics of an all-solid-state secondary battery equipped with a solid electrolyte-containing layer are degraded.
[0052] [Other repeating units]
[0053] Here, polymer A may include repeating units (other repeating units) other than the nitrile group-containing monomer units and aliphatic conjugated diene monomer units described above. Other repeating units are not particularly limited as long as they are repeating units derived from monomers copolymerizable with the nitrile group-containing monomers and aliphatic conjugated diene monomers described above, but examples include ethylenically unsaturated carboxylic acid ester monomer units.
[0054] As for the ethylene unsaturated carboxylic acid ester monomer capable of forming an ethylene unsaturated carboxylic acid ester monomer unit, for example, a monomer consisting of an ester of an ethylene unsaturated monocarboxylic acid or a monomer consisting of a diester of an ethylene unsaturated dicarboxylic acid can be used.
[0055] Here, monomers composed of esters of ethylenically unsaturated monocarboxylic acids may include, for example, (meth)acrylic acid ester monomers. Meanwhile, in the present invention, "(meth)acrylic" means acrylic and / or methacrylic.
[0056] And, as (meth)acrylic acid ester monomers, alkyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, stearyl acrylate; Examples include alkyl methacrylate methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, stearyl methacrylate, glycidyl methacrylate, etc.
[0057] In addition, monomers composed of diesters of ethylenically unsaturated dicarboxylic acids include dialkyl maleates such as diethyl maleate and dibutyl maleate; dialkyl fumarates such as diethyl fumarate and dibutyl fumarate; dialkyl itaconates such as diethyl itaconate and dibutyl itaconate; etc.
[0058] Among these, methyl acrylate, ethyl acrylate, methyl methacrylate, n-butyl acrylate, and dibutyl itaconate are preferred from the perspective of further improving the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery. Meanwhile, regarding the ethylenically unsaturated carboxylic acid ester monomer, one type may be used alone, or two or more types may be used in combination in any ratio.
[0059] In addition, when the total amount of repeating units contained in polymer A is 100 mass%, the content ratio of the ethylene unsaturated carboxylic acid ester monomer unit is preferably 0 mass% or more, 5 mass% or more, 10 mass% or more, 50 mass% or less, more preferably 45 mass% or less, and even more preferably 40 mass% or less. If the content ratio of the ethylene unsaturated carboxylic acid ester monomer unit in polymer A is 50 mass% or less, a slurry composition for a solid electrolyte-containing layer in which the solid electrolyte is well dispersed can be prepared using a binder composition. Furthermore, an all-solid-state secondary battery having a solid electrolyte-containing layer formed using the said slurry composition for a solid electrolyte-containing layer can exhibit sufficiently excellent output characteristics.
[0060] <<Method for preparing polymer A>>
[0061] The method of preparing polymer A is not particularly limited. Polymer A is prepared, for example, by polymerizing a monomer composition containing the monomer described above in an aqueous solvent. Meanwhile, the content ratio of each monomer in the monomer composition can be determined based on the content ratio of the desired monomer unit (repeating unit) in polymer A.
[0062] Meanwhile, regarding the polymerization method, any method such as solution polymerization, suspension polymerization, bulk polymerization, or emulsion polymerization may be used without particular restrictions. Furthermore, any reaction such as ionic polymerization, radical polymerization, living radical polymerization, various condensation polymerizations, or addition polymerization may be used as the polymerization reaction. Additionally, known emulsifiers or polymerization initiators may be used during polymerization as needed.
[0063] <<Properties of Polymer A>>
[0064] [Moon's viscosity]
[0065] And, polymer A has a Mooney viscosity (ML) 1+4The Mooney viscosity (at 100°C) needs to be 65 or higher, preferably 67 or higher, more preferably 70 or higher, even more preferably 75 or higher, preferably less than 200, more preferably less than 180, and even more preferably less than 150. If the Mooney viscosity of polymer A is less than 65, the binding ability and flexibility of polymer A decrease, and thus, a solid electrolyte-containing layer with excellent adhesion and flexibility cannot be formed by a slurry composition for a solid electrolyte-containing layer prepared using a binder composition containing said polymer A. Therefore, even if said solid electrolyte-containing layer is used, excellent output characteristics and high-temperature cycle characteristics cannot be achieved in an all-solid-state secondary battery. Meanwhile, if the Mooney viscosity of polymer A is less than 200, polymer A does not become excessively rigid, and a solid electrolyte-containing layer with sufficient adhesion and flexibility can be formed by a slurry composition for a solid electrolyte-containing layer prepared using a binder composition containing said polymer A. Therefore, the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery can be further improved.
[0066] Meanwhile, the Mooney viscosity of polymer A can be adjusted by changing, for example, the type and ratio of monomers used in the preparation of polymer A, and the preparation method of polymer A (the amount of molecular weight adjusting agent used, the polymer temperature, and the polymer addition rate at the end of polymerization, etc.).
[0067] [Iodine value]
[0068] In addition, it is preferable that the iodine value of polymer A be greater than 30 mg / 100 mg, more preferable that it be 100 mg / 100 mg or higher, even more preferable that it be 200 mg / 100 mg or higher, even more preferable that it be 250 mg / 100 mg or higher, and particularly preferable that it be 280 mg / 100 mg or higher. If the iodine value of polymer A is greater than 30 mg / 100 mg, it is presumed that this is due to an increase in the glass transition temperature or elastic modulus of polymer A, which can improve the adhesion and flexibility of the resulting solid electrolyte-containing layer in a balanced manner, and as a result, further improve the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery. In addition, the upper limit of the iodine value of polymer A is not particularly limited and can be 500 mg / 100 mg or less.
[0069] Meanwhile, the iodine value of polymer A can be adjusted, for example, by changing the type and ratio of monomers used in the preparation of polymer A, and the preparation method of polymer A (such as the presence or absence of hydrogenation addition treatment).
[0070] Other Binding Materials
[0071] Other binders are not particularly limited as long as they differ in composition and / or properties from polymer A, and, for example, polymer compounds such as fluorine-based polymers, diene-based polymers, and nitrile-based polymers may be used.
[0072] Here, as the fluorine-based polymer, diene-based polymer, and nitrile-based polymer, for example, the fluorine-based polymer, diene-based polymer, and nitrile-based polymer described in Japanese Patent Publication No. 2012-243476 may be used.
[0073] In addition, as other binders, the aforementioned polymer compounds may be used alone or in combination.
[0074] <Solvent>
[0075] The solvents that may optionally be included in the binder composition of the present invention are not particularly limited and include, for example, cyclic aliphatic hydrocarbons such as cyclopentane and cyclohexane; aromatic hydrocarbons such as toluene and xylene; butyl butyrate; diisobutyl ketone; and n-butyl ether. These solvents may be used alone or in a mixture of two or more. Among these, xylene and butyl butyrate are preferred from the perspective of increasing the adhesion and flexibility of the solid electrolyte-containing layer while further improving the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery.
[0076] Other ingredients
[0077] Other components that may optionally be included in the binder composition of the present invention include dispersants, leveling agents, defoaming agents, conductive materials, and reinforcing materials. Additionally, for example, if the all-solid-state secondary battery is an all-solid-state lithium-ion secondary battery, lithium salts may be included as other components. These other components are not particularly limited as long as they do not affect the battery reaction.
[0078] Method for preparing a binder composition
[0079] The method for preparing the binder composition of the present invention is not particularly limited. For example, regarding the aqueous dispersion of polymer A as a binder obtained as described above, the binder composition can be prepared by performing solvent substitution as necessary and further adding other binders or other components.
[0080] (Slurry composition for all-solid-state secondary battery electrode composite layer)
[0081] The slurry composition for an electrode composite layer of the present invention comprises a solid electrolyte, an electrode active material, and the binder composition of the present invention described above. More specifically, the slurry composition for an electrode composite layer of the present invention is a composition formed by dispersing and / or dissolving in a solvent a solid electrolyte, an electrode active material, a binder comprising the polymer A described above, and optionally included components other than those mentioned above (optional components).
[0082] In addition, since the slurry composition for the electrode composite layer of the present invention includes the binder composition of the present invention, when an electrode composite layer is produced using the slurry composition for the electrode composite layer of the present invention, excellent output characteristics and high-temperature cycle characteristics can be exhibited in an all-solid-state secondary battery by the electrode having said electrode composite layer.
[0083] Solid Electrolyte
[0084] As for the solid electrolyte, it is not particularly limited as long as it possesses the conductivity of a charge carrier such as lithium ions, and either inorganic solid electrolytes or polymeric solid electrolytes may be used. Meanwhile, the solid electrolyte may be a mixture of an inorganic solid electrolyte and a polymeric solid electrolyte.
[0085] Inorganic Solid Electrolytes
[0086] As for the inorganic solid electrolyte, crystalline inorganic ion conductors, amorphous inorganic ion conductors, or mixtures thereof may be used without being particularly limited. Furthermore, for example, when the all-solid-state secondary battery is an all-solid-state lithium-ion secondary battery, the inorganic solid electrolyte may typically be a crystalline inorganic lithium-ion conductor, an amorphous inorganic lithium-ion conductor, or a mixture thereof.
[0087] Meanwhile, below, as an example, a case is described in which the slurry composition for the electrode composite layer of an all-solid-state secondary battery is a slurry composition for the electrode composite layer of an all-solid-state lithium-ion secondary battery, but the present invention is not limited to the following example.
[0088] And, as crystalline inorganic lithium ion conductors, Li3N, LISICON(Li 14 Zn(GeO4)4), perovskite-type Li 0.5 La 0.5 TiO3, garnet-type Li7La3Zr2O 10 , LIPON(Li 3+y PO 4-x N x ), Thio-LISICON(Li 3.75 Ge 0.25 P 0.75 S4) etc. can be cited.
[0089] In addition, examples of amorphous inorganic lithium ion conductors include glass Li-Si-SO and Li-PS.
[0090] Among the above, as an inorganic solid electrolyte for an all-solid-state lithium-ion secondary battery, an amorphous inorganic lithium-ion conductor is preferred from the perspective of conductivity, and an amorphous sulfide containing Li and P is more preferred. Since an amorphous sulfide containing Li and P has high lithium-ion conductivity, using it as an inorganic solid electrolyte can lower the internal resistance of the battery while simultaneously improving output characteristics.
[0091] Meanwhile, regarding the amorphous sulfide containing Li and P, it is more preferable that the amorphous sulfide is a sulfide glass composed of Li2S and P2S5 from the perspective of lowering the internal resistance of the battery and improving output characteristics, and it is particularly preferable that the amorphous sulfide is a sulfide glass prepared from a mixed raw material of Li2S and P2S5 with a molar ratio of Li2S:P2S5 of 65:35 to 85:15. In addition, regarding the amorphous sulfide containing Li and P, it is preferable that the amorphous sulfide is a sulfide glass ceramic obtained by reacting a mixed raw material of Li2S and P2S5 with a molar ratio of Li2S:P2S5 of 65:35 to 85:15 by a mechanochemical method. Meanwhile, regarding the perspective of maintaining high lithium ion conductivity, it is preferable that the mixed raw material has a molar ratio of Li2S:P2S5 of 68:32 to 80:20.
[0092] And, the lithium ion conductivity of the inorganic solid electrolyte for all-solid-state lithium-ion secondary batteries is not particularly limited and is 1 × 10⁻⁶ -4 It is desirable that it be S / cm or higher, and 1 × 10 -3 It is more desirable to have S / cm or higher.
[0093] Meanwhile, the inorganic solid electrolyte may include at least one sulfide selected from the group consisting of Al2S3, B2S3, and SiS2 as a starting material in addition to the above Li2S and P2S5, to the extent that it does not reduce ion conductivity. Adding such a sulfide can stabilize the glass components in the inorganic solid electrolyte.
[0094] Likewise, in addition to Li2S and P2S5, the inorganic solid electrolyte may contain at least one lithium orthooxate selected from the group consisting of Li3PO4, Li4SiO4, Li4GeO4, Li3BO3, and Li3AlO3. Including such lithium orthooxate can stabilize the free components in the inorganic solid electrolyte.
[0095] In addition, the number average particle size of the inorganic solid electrolyte is preferably 0.1 μm or more, more preferably 0.3 μm or more, preferably 20 μm or less, more preferably 10 μm or less, even more preferably 7 μm or less, and particularly preferably 5 μm or less. If the number average particle size of the inorganic solid electrolyte is 0.1 μm or more, handling is easy, and at the same time, the adhesion of the electrode composite layer formed using the slurry composition for the electrode composite layer can be sufficiently increased. On the other hand, if the number average particle size of the inorganic solid electrolyte is 20 μm or less, the surface area of the inorganic solid electrolyte can be sufficiently secured, and the output characteristics of the all-solid-state secondary battery can be sufficiently improved.
[0096] Meanwhile, in the present invention, the "number average particle size" of the inorganic solid electrolyte and electrode active material can be obtained by observing each of the 100 inorganic solid electrolytes and electrode active materials with an electron microscope, measuring the particle size according to JIS Z8827-1:2008, and calculating the average value.
[0097] Polymer Solid Electrolytes
[0098] Examples of polymeric solid electrolytes include polymers containing polyethylene oxide derivatives and polyethylene oxide derivatives, polymers containing polypropylene oxide derivatives and polypropylene oxide derivatives, phosphate ester polymers, and polymers containing polycarbonate derivatives and polycarbonate derivatives, etc., which contain an electrolyte salt.
[0099] And, for example, when the all-solid-state secondary battery is an all-solid-state lithium-ion secondary battery, the electrolyte salt is not particularly limited and may include lithium fluoride salts such as lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0100] <<Electrode Active Material>>
[0101] The electrode active material is a substance that exchanges electrons at the electrode of an all-solid-state secondary battery. And, for example, when the all-solid-state secondary battery is an all-solid-state lithium-ion secondary battery, a material capable of absorbing and releasing lithium is typically used as the electrode active material.
[0102] Meanwhile, below, as an example, a case is described in which the slurry composition for the electrode composite layer of an all-solid-state secondary battery is a slurry composition for the electrode composite layer of an all-solid-state lithium-ion secondary battery, but the present invention is not limited to the following example.
[0103] In addition, positive electrode active materials for all-solid-state lithium-ion secondary batteries are not particularly limited and may include positive electrode active materials composed of inorganic compounds and positive electrode active materials composed of organic compounds. Meanwhile, the positive electrode active material may be a mixture of inorganic compounds and organic compounds.
[0104] Examples of positive electrode active materials composed of inorganic compounds include transition metal oxides, complex oxides of lithium and transition metals (lithium-containing complex metal oxides), and transition metal sulfides. The above transition metals used include Fe, Co, Ni, and Mn. Specific examples of inorganic compounds used as positive electrode active materials include lithium-containing complex metal oxides such as Co-Ni-Mn lithium-containing complex metal oxide (Li(CoMnNi)O2), Ni-Co-Al lithium-containing complex metal oxide, lithium-containing cobalt oxide (LiCoO2), lithium-containing nickel oxide (LiNiO2), lithium manganate (LiMnO2, LiMn2O4), olivine-type lithium iron phosphate (LiFePO4), and LiFeVO4; transition metal sulfides such as TiS2, TiS3, and amorphous MoS2; and Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, and V6O. 13 Examples include transition metal oxides such as the above. These compounds may be partially elementally substituted.
[0105] Examples of positive electrode active materials composed of organic compounds include polyaniline, polypyrrole, polyacene, disulfide compounds, polysulfide compounds, N-fluoropyridinium salts, etc.
[0106] In addition, allotropes of carbon such as graphite or coke can be used as negative electrode active materials for all-solid-state lithium-ion secondary batteries. Meanwhile, negative electrode active materials composed of allotropes of carbon may also be used in the form of a mixture or coating with metals, metal salts, oxides, etc. In addition, oxides or sulfates of silicon, tin, zinc, manganese, iron, nickel, etc.; metallic lithium; lithium alloys such as Li-Al, Li-Bi-Cd, Li-Sn-Cd; lithium transition metal nitrides; silicon; etc. can also be used as negative electrode active materials.
[0107] The number average particle size of the electrode active material is preferably 0.1 μm or more, more preferably 1 μm or more, preferably 40 μm or less, and more preferably 30 μm or less. If the number average particle size of the electrode active material is 0.1 μm or more, handling is easy, and at the same time, the adhesion of the resulting electrode composite layer can be sufficiently improved. On the other hand, if the number average particle size of the electrode active material is 40 μm or less, the surface area of the electrode active material can be sufficiently secured, and the output characteristics of the all-solid-state secondary battery can be sufficiently improved.
[0108] Meanwhile, the amount of solid electrolyte included in the slurry composition for the electrode composite layer is preferably such that the ratio of the solid electrolyte to the total amount of the electrode active material and the solid electrolyte (100 mass%) is 10 mass% or more, more preferably 20 mass% or more, preferably 70 mass% or less, and more preferably 60 mass% or less. If the ratio of the solid electrolyte is above the lower limit value, sufficient ion conductivity can be secured, and the electrode active material can be effectively utilized to sufficiently increase the capacity of the all-solid-state secondary battery. In addition, if the ratio of the solid electrolyte is below the upper limit value, sufficient amount of the electrode active material can be secured, and the capacity of the all-solid-state secondary battery can be sufficiently increased.
[0109] <<Binding Material>>
[0110] The binder included in the slurry composition for the electrode composite layer comprises at least polymer A described above in the claim "Binder composition for all-solid-state secondary battery".
[0111] In addition, the amount of polymer A included in the slurry composition for the electrode composite layer is preferably 0.1 parts by mass or more per 100 parts by mass of solid electrolyte, more preferably 0.5 parts by mass or more, preferably 7 parts by mass or less, and more preferably 5 parts by mass or less. If the content of polymer A in the slurry composition for the electrode composite layer is 0.1 parts by mass or more per 100 parts by mass of solid electrolyte, the solid electrolyte is sufficiently well dispersed in the slurry composition for the electrode composite layer, thereby further improving the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery. On the other hand, if the content of polymer A in the slurry composition for the electrode composite layer is 7 parts by mass or less per 100 parts by mass of solid electrolyte, the inhibition of the battery reaction by polymer A, which acts as a binder, can be suppressed.
[0112] <<Optional Components and Solvents>>
[0113] Optional components and solvents are not particularly limited. As optional components, for example, components exemplified as “other components” in the claim “Binder composition for all-solid-state secondary batteries” may be used. Additionally, as solvents, for example, solvents exemplified in the claim “Binder composition for all-solid-state secondary batteries” may be used.
[0114] <<Method for preparing a slurry composition for an electrode composite layer>>
[0115] A slurry composition for an electrode composite layer is obtained by mixing each of the components described above. The method of mixing each component of the above slurry composition is not particularly limited, but, for example, a method using a mixing device such as a stirring type, a shaking type, or a rotary type may be used. In addition, a method using a dispersion mixing device such as a homogenizer, a ball mill, a bead mill, a sand mill, a roll mill, and a planetary mixer may be used, and a method using a planetary mixer (such as a rotating mixer), a ball mill, or a bead mill is preferred from the view that it can suppress the aggregation of the electrode active material and / or solid electrolyte.
[0116] (Slurry composition for solid electrolyte layer of all-solid-state secondary battery)
[0117] The slurry composition for a solid electrolyte layer of the present invention comprises a solid electrolyte and the binder composition of the present invention described above. More specifically, the slurry composition for a solid electrolyte layer of the present invention is a composition formed by dispersing and / or dissolving in a solvent a solid electrolyte, a binder comprising the polymer A described above, and optionally a component other than those mentioned above (optional component).
[0118] In addition, since the slurry composition for a solid electrolyte layer of the present invention includes the binder composition of the present invention, when a solid electrolyte layer is manufactured using the slurry composition for a solid electrolyte layer of the present invention, excellent output characteristics and high-temperature cycle characteristics can be achieved in an all-solid-state secondary battery.
[0119] Solid Electrolyte
[0120] As for the solid electrolyte, the same as that exemplified in the “Slurry Composition for All-Solid Secondary Battery Electrode Composite Layer” may be used. Also, the suitable examples and suitable characteristics of the solid electrolyte included in the slurry composition for the solid electrolyte layer are the same as the suitable examples and suitable characteristics of the solid electrolyte included in the slurry composition for the electrode composite layer.
[0121] <Binding Material>
[0122] The binder included in the slurry composition for the solid electrolyte layer comprises at least polymer A described above in the claim "Binder composition for all-solid-state secondary battery".
[0123] In addition, the amount of polymer A included in the slurry composition for the solid electrolyte layer is preferably 0.1 parts by mass or more per 100 parts by mass of the solid electrolyte, more preferably 0.5 parts by mass or more, preferably 7 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less. If the content of polymer A in the slurry composition for the solid electrolyte layer is 0.1 parts by mass or more per 100 parts by mass of the solid electrolyte, the solid electrolyte is sufficiently well dispersed in the slurry composition for the solid electrolyte layer, thereby further improving the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery. On the other hand, if the content of polymer A in the slurry composition for the solid electrolyte layer is 7 parts by mass or less per 100 parts by mass of the solid electrolyte, the inhibition of the battery reaction by the polymer A acting as a binder can be suppressed.
[0124] <<Optional Components and Solvents>>
[0125] Optional components and solvents are not particularly limited. As optional components, for example, dispersants, leveling agents, defoaming agents, etc., exemplified as “other components” in the section “Binder Composition for All-Solid-State Secondary Batteries” may be used. Additionally, as solvents, for example, solvents exemplified in the section “Binder Composition for All-Solid-State Secondary Batteries” may be used.
[0126] (Electrode for all-solid-state secondary battery)
[0127] An electrode for an all-solid-state secondary battery can be manufactured using the slurry composition for an electrode composite layer of the present invention described above. For example, by forming an electrode composite layer on a current collector using the slurry composition for an electrode composite layer of the present invention, an electrode having a current collector and an electrode composite layer on the current collector can be obtained. Furthermore, according to the electrode having an electrode composite layer formed from the slurry composition for an electrode composite layer of the present invention, excellent output characteristics and high-temperature cycle characteristics can be exhibited in an all-solid-state secondary battery.
[0128] <Whole House>
[0129] The current collector is not particularly limited as long as it is made of a material that is electrically conductive and electrochemically durable; however, from the perspective of heat resistance, metallic materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, and platinum are preferred. Among these, aluminum is particularly preferred for the positive electrode, and copper is particularly preferred for the negative electrode. The shape of the current collector is not particularly limited, but it is preferred to be in the form of a sheet with a thickness of approximately 0.001 mm or more and 0.5 mm or less. To increase the adhesion strength with the electrode composite layer, it is preferable to use the current collector after pre-roughening treatment. Roughening methods include mechanical polishing, electrolytic polishing, and chemical polishing. In mechanical polishing, a polishing cloth with abrasive particles attached, a grinding wheel, an emery buff, or a wire brush equipped with steel wire is used. Additionally, an intermediate layer may be formed on the surface of the current collector to increase the adhesion strength or conductivity between the current collector and the electrode composite layer.
[0130] <Electrode composite layer>
[0131] As described above, the electrode composite layer is formed using the slurry composition for the electrode composite layer of the present invention. Specifically, the electrode composite layer is composed of a dried product of the slurry composition for the electrode composite layer of the present invention, and the electrode composite layer contains at least a solid electrolyte, an electrode active material, and polymer A as a binder. Meanwhile, each component included in the electrode composite layer is one that was included in the slurry composition for the electrode composite layer, and the appropriate abundance ratio of each of those components is the same as the appropriate abundance ratio of each component in the slurry composition for the electrode composite layer.
[0132] Method for manufacturing electrodes for all-solid-state secondary batteries
[0133] The electrode is manufactured, for example, by passing through a process of applying the slurry composition for the electrode composite layer of the present invention onto a current collector (coating process) and a process of drying the slurry composition for the electrode composite layer applied onto the current collector to form an electrode composite layer (drying process).
[0134] Coating Process
[0135] The method of applying the slurry composition for the electrode composite layer onto the current collector is not particularly limited and known methods may be used. Specifically, examples of application methods include the doctor blade method, dip method, reverse roll method, direct roll method, gravure method, extrusion method, brush application, etc.
[0136] In addition, the amount of coating is not specifically limited and can be appropriately set according to the desired thickness of the electrode composite layer, etc.
[0137] <<Drying Process>>
[0138] The method for drying the slurry composition for the electrode composite layer on the current collector is not particularly limited and any known method may be used. Specifically, drying methods include drying with hot air, hot air, or low-humidity air, vacuum drying, and drying by irradiation with (far)infrared rays or electron beams. It is desirable to adjust the drying conditions so that the solvent volatilizes as quickly as possible, under conditions where stress concentration does not occur, causing cracks in the electrode composite layer or peeling off from the current collector.
[0139] Regarding the specific drying temperature, it is preferable to have a temperature of 50°C or higher and 250°C or lower, and 80°C or higher and 200°C or lower. By maintaining the above range, it becomes possible to suppress the thermal decomposition of the binder containing polymer A and form a good electrode composite layer. As for the drying time, there is no particular limitation, but it is typically carried out in the range of 10 minutes or more and 60 minutes or less.
[0140] Meanwhile, the electrode may be stabilized by pressing it after drying. Examples of pressing methods include die pressing and calendering, but are not limited to these.
[0141] The mass per unit area of the electrode composite layer in the electrode obtained as described above is not particularly limited, but is 1.0 mg / cm² 2 Above 20.0 mg / cm² 2 It is preferable that it be less than or equal to 5.0 mg / cm² 2 Above 15.0 mg / cm² 2 It is more desirable to be less than this.
[0142] (Solid electrolyte layer for all-solid-state secondary batteries)
[0143] A solid electrolyte layer can be produced using the slurry composition for a solid electrolyte layer of the present invention described above. Furthermore, according to the solid electrolyte layer produced using the slurry composition for a solid electrolyte layer of the present invention, excellent output characteristics and high-temperature cycle characteristics can be exhibited in an all-solid-state secondary battery.
[0144] Here, the solid electrolyte layer is formed using the slurry composition for a solid electrolyte layer of the present invention as described above. Specifically, the solid electrolyte layer is composed of a dried product of the slurry composition for a solid electrolyte layer of the present invention, and the solid electrolyte layer contains at least a solid electrolyte and polymer A as a binder. Meanwhile, each component contained in the solid electrolyte layer is one that was contained in the slurry composition for a solid electrolyte layer, and the appropriate abundance ratio of each of those components is the same as the appropriate abundance ratio of each component in the slurry composition for a solid electrolyte layer.
[0145] Method for manufacturing a solid electrolyte layer for an all-solid-state secondary battery
[0146] Methods for forming a solid electrolyte layer include, for example, the following methods.
[0147] 1) A method for forming a solid electrolyte layer on an electrode by applying a slurry composition for a solid electrolyte layer according to the present invention onto an electrode (typically, the surface of an electrode composite layer; hereinafter the same) and then drying it;
[0148] 2) A method for forming a solid electrolyte layer on an electrode by applying a slurry composition for a solid electrolyte layer according to the present invention onto a substrate, drying it, and then transferring the obtained solid electrolyte layer onto an electrode; and,
[0149] 3) A method for forming a self-supporting solid electrolyte layer by applying the slurry composition for a solid electrolyte layer of the present invention onto a substrate and drying the resulting dried product of the slurry composition for a solid electrolyte layer to form a powder, and then forming the obtained powder into a layer.
[0150] For the methods of coating, drying, transfer, grinding, molding, etc. used in the methods described in 1) to 3) above, all known methods may be adopted.
[0151] In addition, the thickness of the solid electrolyte layer obtained as described above is not particularly limited, but it is preferably 10 μm or more and 500 μm or less, more preferably 20 μm or more and 300 μm or less, and even more preferably 30 μm or more and 200 μm or less. By having the thickness of the solid electrolyte layer within the range described above, the internal resistance of the all-solid-state secondary battery can be reduced, thereby enabling the all-solid-state secondary battery to exhibit superior output characteristics. Meanwhile, by having a thickness of 10 μm or more of the solid electrolyte layer, short circuits between the positive and negative electrodes inside the all-solid-state secondary battery can be sufficiently suppressed.
[0152] (All-solid-state secondary battery)
[0153] The all-solid-state secondary battery of the present invention comprises at least one of an electrode having an electrode composite layer formed using the slurry composition for an electrode composite layer of the present invention described above, and a solid electrolyte layer formed using the slurry composition for a solid electrolyte layer of the present invention described above. That is, the all-solid-state secondary battery of the present invention comprises a positive electrode having a positive electrode composite layer, a negative electrode having a negative electrode composite layer, and a solid electrolyte layer, and at least one selected from the group consisting of a positive electrode composite layer, a negative electrode composite layer, and a solid electrolyte layer is formed using a slurry composition for a solid electrolyte containing layer (slurry composition for an electrode composite layer or slurry composition for a solid electrolyte layer) comprising the binder composition of the present invention described above.
[0154] Furthermore, the all-solid-state secondary battery of the present invention has excellent battery characteristics, such as output characteristics and high-temperature cycle characteristics, because at least one of the positive electrode composite layer, the negative electrode composite layer, and / or the solid electrolyte layer includes polymer A as a binder derived from the binder composition of the present invention.
[0155] Meanwhile, as for electrodes (positive and negative electrodes) other than the electrode having an electrode composite layer formed using the slurry composition for the electrode composite layer of the present invention that can be used in the all-solid-state secondary battery of the present invention, any electrode may be used as long as it does not have an electrode composite layer formed using the slurry composition for the electrode composite layer of the present invention.
[0156] In addition, any solid electrolyte layer other than the solid electrolyte layer formed using the slurry composition for a solid electrolyte layer of the present invention, which can be used in the all-solid-state secondary battery of the present invention, is not particularly limited as long as it is not formed using the slurry composition for a solid electrolyte layer of the present invention, and any solid electrolyte layer may be used.
[0157] In addition, the all-solid-state secondary battery of the present invention can be obtained by stacking a positive electrode and a negative electrode such that the positive electrode composite layer of the positive electrode and the negative electrode composite layer of the negative electrode face each other with a solid electrolyte layer interposed therebetween, and then obtaining a laminated body by applying pressure as desired, and then placing it in a battery container and sealing it, either in that state or by winding or folding it according to the battery shape. Meanwhile, if necessary, an overcurrent protection element such as expanded metal, a fuse, or a PTC element, or a lead plate may be placed in the battery container to prevent pressure rise inside the battery and overcharging / discharging. The shape of the battery may be any of the following: coin type, button type, sheet type, cylindrical type, prismatic type, or flat type.
[0158] Examples
[0159] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. Meanwhile, in the following description, "%" and "parts" indicating amounts are based on mass unless otherwise specified.
[0160] And, in the examples and comparative examples, the Mooney viscosity (ML) of the polymer 1+4 The composition, iodine value, adhesion and flexibility of the negative electrode composite layer, and the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery were measured and evaluated by the following methods.
[0161] Mooney viscosity (ML) 1+4 , 100℃)>
[0162] After coagulating the aqueous dispersion of the polymer with methanol, the polymer was vacuum dried at 60°C for 12 hours to obtain a dry polymer. 40g of the obtained dry polymer was used and measured at 100°C in accordance with JIS K6300-1.
[0163] <Creation>
[0164] 100g of the aqueous dispersion of the polymer was coagulated with 1L of methanol, and then vacuum dried at 60℃ for 12 hours to obtain a dry polymer. The obtained dry polymer 1 The content ratio (mass%) of repeating units (monomer units) included in the polymer was calculated based on the peak areas of the obtained spectrum and analyzed by H-NMR.
[0165] Iodine value
[0166] 100g of an aqueous dispersion of the polymer was coagulated with 1L of methanol, and then vacuum dried at 60°C for 12 hours to obtain a dry polymer. Then, the iodine value of the obtained dry polymer was measured according to JIS K6235 (2006).
[0167] <Adhesion>
[0168] The negative electrode was cut into a rectangular shape measuring 1.0 cm in width × 10 cm in length to serve as a test specimen. Subsequently, cellophane tape (as specified in JIS Z1522) was attached to the surface of the negative electrode composite layer with the surface of the negative electrode composite layer facing downward. Then, the stress was measured when the cellophane tape was peeled off from one end of the test specimen in a 180° direction at a speed of 50 mm / min. This measurement was performed a total of 10 times, and the average value was calculated and set as the peel strength (N / m), which was evaluated according to the following criteria. A higher peel strength value indicates that the negative electrode composite layer is more firmly adhered to the current collector.
[0169] A: Peel strength of 20.0 N / m or higher
[0170] B: Peel strength is 15.0 N / m or more and less than 20.0 N / m
[0171] C: Peel strength 10.0 N / m or more and less than 15.0 N / m
[0172] D: Peel strength less than 10.0 N / m
[0173] Flexibility
[0174] Regarding the negative electrode, a bendability test was performed according to the mandrel test (JIS K 5600 (1999)). Specifically, the negative electrode was wrapped around a mandrel having diameters of 5.0 mmφ, 4.0 mmφ, and 3.0 mmφ with the negative electrode composite layer facing outward, and after wrapping, the presence or absence of cracks occurring on the surface of the negative electrode composite layer was observed using a digital microscope and evaluated according to the following criteria. The smaller the diameter of the mandrel at which cracks occur, the better the bendability of the negative electrode composite layer. If no cracks occur even when using a mandrel with a diameter of 3.0 mmφ, it means that the negative electrode composite layer has particularly excellent bendability.
[0175] A: No cracks occur even at 3.0 mmφ.
[0176] B: Cracks occur at 3.0 mmφ, but not at 4.0 mmφ.
[0177] C: Cracks occur at 4.0 mmφ, but not at 5.0 mmφ.
[0178] D: Cracks occur at 5.0 mmφ.
[0179] <Output Characteristics>
[0180] A 10-cell all-solid-state secondary battery was charged to 4.3V using the constant current method at 0.1C and then discharged to 3.0V at 0.1C to determine the 0.1C discharge capacity. Subsequently, the battery was charged to 4.3V at 0.1C and then discharged to 3.0V at 5C to determine the 5C discharge capacity. The average value of the 0.1C discharge capacities of the 3 cells was designated as discharge capacity a, and the average value of the 10C discharge capacities of the 3 cells was designated as discharge capacity b. The ratio of discharge capacity b to discharge capacity a (capacity ratio) = discharge capacity b / discharge capacity a × 100 (%) was calculated and evaluated according to the following criteria. A higher capacity ratio indicates superior output characteristics.
[0181] A: Volume ratio of 50% or more
[0182] B: Volume ratio is 40% or more and less than 50%
[0183] C: Volume ratio is 30% or more and less than 40%
[0184] D: Volume ratio less than 30%
[0185] High-temperature cycle characteristics
[0186] The obtained all-solid-state secondary battery was charged from 3V to 4.3V at 0.1C at 60°C, and then discharged from 4.3V to 3V at 0.1C, and this charging and discharging process was repeated for 100 cycles. The ratio of the 0.1C discharge capacity at the 100th cycle to the 0.1C discharge capacity at the 5th cycle was calculated as a percentage and was evaluated according to the following criteria. A higher value for the capacity retention rate indicates less reduction in discharge capacity and superior high-temperature cycle characteristics.
[0187] A: Dose retention rate is 60% or higher
[0188] B: Dose retention rate is 50% or more and less than 60%
[0189] C: Dose retention rate is 40% or more but less than 50%
[0190] D: Dose retention rate is 30% or more but less than 40%
[0191] (Example 1)
[0192] <Preparation of a binder composition containing polymer A>
[0193] In a reactor with a capacity of 10 liters, 100 parts of ion-exchanged water, 20 parts of acrylonitrile as a nitrile group-containing monomer, and 80 parts of 1,3-butadiene as an aliphatic conjugated diene monomer were added, and 2 parts of potassium oleate as an emulsifier, 0.1 parts of potassium phosphate as a stabilizer, and 0.5 parts of 2,2',4,6,6'-pentamethylheptane-4-thiol (TIBM) as a molecular weight adjuster were added. Subsequently, 0.35 parts of potassium persulfate as a polymerization initiator were added to the reaction mixture, and emulsion polymerization was carried out at 30°C to copolymerize 1,3-butadiene and acrylonitrile.
[0194] When the polymerization conversion rate reached 90%, 0.2 parts of hydroxylamine sulfate were added to the reactor to stop the polymerization. Subsequently, the mixture was heated and steam distilled at approximately 70°C under reduced pressure to recover the residual monomer, after which 2 parts of alkylated phenol were added as an anti-aging agent to obtain an aqueous dispersion of polymer A (a copolymer of 1,3-butadiene and acrylonitrile).
[0195] Afterward, the system was conditioned to a nitrogen atmosphere and concentrated at room temperature using an evaporator until the solid content reached 40%. Using the aqueous dispersion of polymer A after this concentration, the Mooney viscosity, composition, and iodine value of polymer A were measured. The results are shown in Table 1.
[0196] Then, xylene was added to the aqueous dispersion of polymer A after concentration, and water was evaporated under reduced pressure to obtain a binder composition (solid content: 8 to 10%) containing polymer A and xylene.
[0197] <Binder composition containing polymer B>
[0198] A water dispersion of the polymer was obtained in the same manner as the "binder composition containing polymer A" described above, except that the amount of acrylonitrile was changed to 22 parts and the amount of 1,3-butadiene was changed to 78 parts. As a result of measuring the composition of the polymer using the obtained water dispersion of the polymer, the polymer contained 22% acrylonitrile units and 78% 1,3-butadiene units.
[0199] Next, 400 mL of the obtained aqueous dispersion of the polymer (total solid content: 48 g) was placed into a 1-liter autoclave equipped with a stirrer, and nitrogen gas was flowed for 10 minutes to remove dissolved oxygen from the aqueous dispersion. Subsequently, as a hydrogenation reaction catalyst, 50 mg of palladium acetate was dissolved in 180 mL of water to which 4 molar nitric acid relative to Pd was added, and added. After purging the system with hydrogen gas twice, the contents of the autoclave were heated to 50°C under pressure with hydrogen gas up to 3 MPa, and the hydrogenation reaction was carried out for 6 hours to obtain an aqueous dispersion of polymer B (hydrogenated nitrile rubber).
[0200] Afterwards, the system was set to a nitrogen atmosphere and concentrated at room temperature using an evaporator until the solid content concentration reached 40%. Using the aqueous dispersion of polymer B after this concentration, the Mooney viscosity and iodine value of polymer B were measured, and the Mooney viscosity of polymer B was 70 and the iodine value was 7. Meanwhile, from the iodine value, it was confirmed that the content ratio of aliphatic conjugated diene monomer units (1,3-butadiene units) in polymer B was less than 40 mass%.
[0201] Then, xylene was added to the aqueous dispersion of polymer B after concentration, and water was evaporated under reduced pressure to obtain a binder composition (solid content: 8 to 10%) containing polymer B and xylene.
[0202] <Preparation of Slurry Composition for Negative Electrode Composite Layer>
[0203] 100 parts of graphite (number average particle size: 20 μm) as a negative electrode active material, 50 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5 = 70 mol% / 30 mol%, number average particle size: 0.4 μm) as a solid electrolyte, and 3 parts (equivalent to solid content) of a binder composition containing the above polymer A were mixed, and xylene was added to the obtained mixture to prepare a composition with a solid content concentration of 65%. This composition was mixed using a rotational mixer and further adjusted to a solid content concentration of 60% with xylene to obtain a slurry composition for a negative electrode composite layer.
[0204] <Preparation of Slurry Composition for Positive Electrode Combined Layer>
[0205] Active material NMC532 of the Co-Ni-Mn lithium composite oxide system as a positive electrode active material (LiNi 5 / 10 Co 2 / 10 Mn 3 / 10 100 parts of O2 (number average particle size: 10.0 μm), 50 parts of sulfide glass composed of Li2S and P2S5 as a solid electrolyte (Li2S / P2S5 = 70 mol% / 30 mol%, number average particle size: 0.4 μm), 3 parts of acetylene black as a conductive material, and 2 parts of a binder composition (equivalent to solid content) containing the above polymer B were mixed, and xylene was added to the obtained mixture to prepare a composition with a solid content concentration of 75%. This composition was mixed using a rotating mixer and further adjusted to a solid content concentration of 70% with xylene to obtain a slurry composition for a positive electrode composite layer.
[0206] Fabrication of Solid Electrolyte Layer
[0207] 100 parts of a sulfide glass composed of Li2S and P2S5 as a solid electrolyte (Li2S / P2S5 = 70 mol% / 30 mol%, number average particle size: 0.4 μm) and 2 parts of a binder composition (equivalent to solid content) containing the above polymer B were mixed, and xylene was added to the resulting mixture to prepare a composition with a solid content concentration of 60%. This composition was mixed using a rotational mixer to obtain a slurry composition for a solid electrolyte layer. This slurry composition for a solid electrolyte layer was dried on a release sheet as a substrate, and the dried material peeled off from the release sheet was ground and crushed using a mortar and pestle to obtain a powder. 0.05 mg of the obtained powder was placed into a 10 mmφ mold and molded under a pressure of 200 MPa to obtain a pellet (solid electrolyte layer) with a thickness of 500 μm.
[0208] The Production of the Play
[0209] By applying the slurry composition for the negative electrode composite layer to the surface of the copper foil serving as a current collector and drying at 120°C for 20 minutes, a negative electrode composite layer (mass per unit area: 10.0 mg / cm²) is formed on one side of the copper foil serving as a current collector. 2 A negative pole having ) was obtained.
[0210] Adhesion and flexural strength were evaluated using this negative electrode. The results are shown in Table 1.
[0211] Production of Straight Drama
[0212] By applying the slurry composition for the positive electrode composite layer to the surface of the aluminum foil serving as a current collector and drying at 120°C for 30 minutes, a positive electrode composite layer (mass per unit area: 18.0 mg / cm²) is formed on one side of the aluminum foil serving as a current collector. 2 Obtained a positive pole having ).
[0213] Manufacturing of All-Solid State Secondary Batteries
[0214] The negative electrode and positive electrode obtained as described above were each stamped to a diameter of 10 mmφ. A solid electrolyte layer obtained as described above was placed between the positive and negative electrodes after stamping (at this time, the electrode composite layer of each electrode is in contact with the solid electrolyte layer), and a laminate for an all-solid-state secondary battery was obtained by pressing with a pressure of 200 MPa. The obtained laminate was placed in an evaluation cell (confining pressure: 40 MPa) to obtain an all-solid-state secondary battery. Then, the output characteristics and high-temperature cycle characteristics of the obtained all-solid-state secondary battery were evaluated. The results are shown in Table 1.
[0215] (Examples 2 to 4)
[0216] Except for changing the amounts of acrylonitrile and 1,3-butadiene used in the preparation of polymer A to 12 parts and 88 parts (Example 2), 27 parts and 73 parts (Example 3), and 8 parts and 92 parts (Example 4), respectively, when preparing the binder composition containing polymer A, the binder composition (polymers A and B), the slurry composition for the negative electrode composite layer, the slurry composition for the positive electrode composite layer, the slurry composition for the solid electrolyte layer, the solid electrolyte layer, the negative electrode, the positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results are shown in Table 1.
[0217] (Examples 5 ~ 6)
[0218] Except for changing the amount of molecular weight adjuster (TIBM) used in the preparation of polymer A to 0.33 parts (Example 5) and 0.15 parts (Example 6) when preparing the binder composition containing polymer A, the binder composition (polymers A and B), the slurry composition for the negative electrode composite layer, the slurry composition for the positive electrode composite layer, the slurry composition for the solid electrolyte layer, the solid electrolyte layer, the negative electrode, the positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results are shown in Table 1.
[0219] (Example 7)
[0220] In the preparation of a binder composition containing polymer A, 20 parts of acrylonitrile as a nitrile group-containing monomer, 60 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, and 20 parts of n-butyl acrylate as an ethylenically unsaturated carboxylic acid ester monomer were used as monomers for preparing polymer A, and the amount of molecular weight adjuster (TIBM) used for preparing polymer A was changed to 0.30 parts; otherwise, the process was carried out in the same manner as in Example 1, and a binder composition (polymers A and B), a slurry composition for a negative electrode composite layer, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a solid electrolyte layer, a negative electrode, a positive electrode, and an all-solid-state secondary battery were prepared, and measurements and evaluations were performed. The results are shown in Table 1.
[0221] (Example 8)
[0222] Except for changing n-butyl acrylate as an ethylenically unsaturated carboxylic acid ester monomer to ethyl acrylate when preparing a binder composition containing polymer A, the binder composition (polymers A and B), a slurry composition for a negative electrode composite layer, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a solid electrolyte layer, a negative electrode, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 7, and measurements and evaluations were performed. The results are shown in Table 1.
[0223] (Example 9)
[0224] Except for using a binder composition containing polymer A instead of a binder composition containing polymer B when fabricating the solid electrolyte layer, the same as in Example 1 was used to prepare the binder composition (polymers A and B), the slurry composition for the negative electrode composite layer, the slurry composition for the positive electrode composite layer, the slurry composition for the solid electrolyte layer, the solid electrolyte layer, the negative electrode, the positive electrode, and an all-solid-state secondary battery, and measurements and evaluations were performed. The results are shown in Table 2.
[0225] (Examples 10 ~ 11)
[0226] Except for using diisobutyl ketone (Example 10) and n-butyl ether (Example 11) instead of xylene when preparing the binder composition containing polymer A and the slurry composition for the negative electrode composite layer, respectively, the same procedure as in Example 1 was performed to prepare the binder composition (polymers A and B), the slurry composition for the negative electrode composite layer, the slurry composition for the positive electrode composite layer, the slurry composition for the solid electrolyte layer, the solid electrolyte layer, the negative electrode, the positive electrode, and an all-solid-state secondary battery, and measurements and evaluations were performed. The results are shown in Table 2.
[0227] (Comparative Examples 1 ~ 2)
[0228] Except for changing the amounts of acrylonitrile and 1,3-butadiene used in the preparation of polymer A to 35 parts and 65 parts (Comparative Example 1) and 2 parts and 98 parts (Comparative Example 2), respectively, when preparing the binder composition containing polymer A, the binder composition (polymers A and B), the slurry composition for the negative electrode composite layer, the slurry composition for the positive electrode composite layer, the slurry composition for the solid electrolyte layer, the solid electrolyte layer, the negative electrode, the positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and measurements and evaluations were performed. The results are shown in Table 2.
[0229] (Comparative Example 3)
[0230] Except for not preparing a binder composition containing polymer A and using a binder composition containing polymer B instead of a binder composition containing polymer A when preparing a slurry composition for a negative electrode composite layer, the same procedure as in Example 1 was followed to prepare a binder composition containing polymer B, a slurry composition for a negative electrode composite layer, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a solid electrolyte layer, a negative electrode, a positive electrode, and an all-solid-state secondary battery, and measurements and evaluations were performed. The results are shown in Table 2.
[0231] (Comparative Example 4)
[0232] A binder composition containing polymer B, a slurry composition for the negative electrode composite layer, a slurry composition for the positive electrode composite layer, a slurry composition for the solid electrolyte layer, a solid electrolyte layer, a negative electrode, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that a binder composition containing polymer A was not prepared, and when preparing the slurry composition for the negative electrode composite layer, a binder composition containing nitrile rubber prepared as follows was used instead of the binder composition containing polymer A. Measurements and evaluations were then performed. The results are shown in Table 2.
[0233] <Preparation of a binder composition containing nitrile rubber>
[0234] A binder composition (solid content: 8 to 10%) containing nitrile rubber and xylene was obtained by making it identical to the binder composition containing polymer A described above, except that the amounts of acrylonitrile and 1,3-butadiene were changed to 22 parts and 78 parts, and the amount of molecular weight adjuster (TIBM) was changed to 0.37 parts. Meanwhile, the Mooney viscosity, iodine value, and composition of the nitrile rubber were measured, and the Mooney viscosity of the nitrile rubber was 50, the iodine value was 366, and the nitrile rubber contained 22% acrylonitrile units and 78% 1,3-butadiene units.
[0235] Meanwhile, among Tables 1 and 2 shown below,
[0236] "AN" represents an acrylonitrile unit, and
[0237] "BD" represents a 1,3-butadiene unit, and
[0238] "H-BD" represents a repeating unit formed by hydrogenating a 1,3-butadiene unit, and
[0239] "BA" represents an n-butyl acrylate unit, and
[0240] "EA" represents an ethyl acrylate unit, and
[0241] "DIK" represents diisobutyl ketone,
[0242] "BE" represents n-butyl ether,
[0243] "Polar" refers to the polar composite layer,
[0244] "Solid" refers to a solid electrolyte layer.
[0245]
[0246]
[0247] From Tables 1 and 2, it can be seen that in Examples 1 to 11, polymer A, which contains nitrile group-containing monomer units and aliphatic conjugated diene monomer units in proportions within a predetermined range as a binder, and has a Mooney viscosity greater than or equal to a predetermined value, a negative electrode composite layer with excellent adhesion and flexibility is obtained, and an all-solid-state secondary battery with excellent output characteristics and high-temperature cycle characteristics is obtained.
[0248] Meanwhile, from Table 2, it can be seen that in Comparative Examples 1 to 3, in which a polymer containing at least one of a nitrile group-containing monomer unit and an aliphatic conjugated diene monomer unit is used as a binder in a ratio outside a predetermined range, and in Comparative Example 4, in which a polymer with a Mooney viscosity of less than or equal to a predetermined value is used, the adhesion and flexibility of the negative electrode composite layer are reduced, and at the same time, the output characteristics and high-temperature cycle characteristics of the all-solid-state secondary battery are reduced.
[0249] Industrial applicability
[0250] According to the present invention, a binder composition for an all-solid-state secondary battery capable of forming a solid electrolyte-containing layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in the all-solid-state secondary battery can be provided.
[0251] In addition, according to the present invention, a slurry composition for an electrode composite layer for an all-solid-state secondary battery can be provided, which can form an electrode composite layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0252] In addition, according to the present invention, a slurry composition for a solid electrolyte layer of a solid-state secondary battery can be provided, which can form a solid electrolyte layer capable of exhibiting excellent output characteristics and high-temperature cycle characteristics in a solid-state secondary battery.
[0253] In addition, according to the present invention, an all-solid-state secondary battery with excellent output characteristics and high-temperature cycle characteristics can be provided.
Claims
Claim 1 A binder composition for an all-solid-state secondary battery comprising polymer A, wherein polymer A comprises nitrile group-containing monomer units and aliphatic conjugated diene monomer units, wherein the content ratio of the nitrile group-containing monomer units in polymer A is 5 mass% or more and 30 mass% or less, and the content ratio of the aliphatic conjugated diene monomer units is 40 mass% or more and 95 mass% or less, and wherein the Mooney viscosity (ML) of polymer A 1+4 A binder composition for an all-solid-state secondary battery, wherein the iodine value (at , 100℃) is 65 or higher and the iodine value of the polymer A is 250 mg / 100 mg or higher. Claim 2 A binder composition for an all-solid-state secondary battery according to claim 1, wherein the content ratio of ethylenically unsaturated carboxylic acid ester monomer units in the polymer A is 0 mass% or more and 50 mass% or less. Claim 3 A binder composition for an all-solid-state secondary battery according to claim 1, further comprising a solvent, wherein the solvent contains at least one of xylene and butyl butyrate. Claim 4 A slurry composition for an all-solid-state secondary battery electrode composite layer comprising a solid electrolyte, an electrode active material, and a binder composition for an all-solid-state secondary battery described in claim 1. Claim 5 A slurry composition for an all-solid-state secondary battery electrode composite layer according to claim 4, wherein the solid electrolyte is an amorphous sulfide containing Li and P. Claim 6 A slurry composition for an all-solid-state secondary battery electrode composite layer according to claim 4, wherein the solid electrolyte is a sulfide glass composed of Li2S and P2S5. Claim 7 A slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, comprising a solid electrolyte and a binder composition for an all-solid-state secondary battery as described in claim 1. Claim 8 A slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, wherein, in claim 7, the solid electrolyte is an amorphous sulfide containing Li and P. Claim 9 A slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, wherein, in claim 7, the solid electrolyte is a sulfide glass composed of Li2S and P2S5. Claim 10 An all-solid-state secondary battery comprising at least one of an electrode having an electrode composite layer formed using a slurry composition for an all-solid-state secondary battery electrode composite layer described in any one of claims 4 to 6, and a solid electrolyte layer formed using a slurry composition for an all-solid-state secondary battery solid electrolyte layer described in any one of claims 7 to 9. Claim 11 delete
Citation Information
Patent Citations
Electrode for all-solid-state secondary batteries and method for producing same
KR1020150002589A
Binder composition for secondary battery electrode, slurry composition for secondary battery electrode, electrode for secondary battery, and secondary battery
KR1020180003619A
Binder composition for all-solid-state battery, slurry composition for all-solid-state battery, electrode for all-solid-state battery, and all-solid-state battery
WO2018047821A1
